Psikosufistik sebagai Pendekatan Penanganan Covid-19 (Studi pada Masyarakat Kabupaten Kediri, Jawa Timur) - Akhmad Hasan Saleh (Journal of Sufism and Psychotherapy, 2022)
The spread of Covid-19 has been designated as a pandemi because its spread has reached various parts of the world. This situation causes increased anxiety and stres in society. Stress conditions can actually have a negative impact on the immune system, making a person more susceptible to diseases, including Covid-19. This study aims to examine the handling of Covid-19 from the therapeutic aspect to deal with stres with a religious approach, such as prayer, sincerity, and resignation with psychological energy, where this is part of the psychosufistic approach. The research method used is descriptive qualitative with interviews with community members who are members of a jama'i dhikr group affected by the spread of Covid-19. This research describes what it is about the condition of people who are doing psychosufistic therapy in handling Covid-19. The results of this study indicate that based on the results of a survey on the psychological condition of the community, the spread of Covid-19 has increased anxiety in the people of Kediri which caused a decrease in immunity in some of the people surveyed. However, psychosufistic therapy through jama'i dhikr is very effective in dealing with Covid-19. Through this therapy there is a change in the mindset of the community, thereby reducing the anxiety that occurred before. People who are members of the congregation of dhikr jama'i also experience an increase in immunity which causes the spread of Covid-19 among them to be low. Through psychosufistic therapy, people affected by Covid-19 also experience rapid recovery.